Examining Characteristics of Bind Variables in Oracle Database - Zarinkhail, Mohammad Shuaib; Shahidzay, Amir Kror (Journal of Natural Sciences – Kabul University, 2022)
The use of variables in computer programming is crucial for enhancing program performance. Variables are widely employed in database programming for queries. Similar to other variables, bind variables are used in databases to improve performance. When bind variables are implemented, the program interpreter uses the address of data instead of actual data values, which prevents repetitive processes in a program or query. This research includes practical examples from Oracle databases, comparing the use and non-use of bind variables. The findings highlight significant performance time differences when bind variables are utilized.